Autologous Priming Technique to Reduce Blood Transfusion in Pediatric Cardiopulmonary Bypass - Ostrowsky, Jacob (J Extra Corpor Technol, 2006)
Excessive hemodilution during cardiopulmonary bypass is associated with decreased oxygen carrying capacity, edema, and organ dysfunction. The use of blood products is often necessary to prime the extracorporeal circuit for pediatric cardiac surgical patients. However, the use of blood products carries serious risks both in the acute and long-term aspects of patient care. Autologous priming of the extracorporeal circuit used in conjunction with ultrafiltration, pharmacologic manipulation, and cell salvage may decrease the need for blood transfusion in the pediatric cardiac surgical population. We have developed a technique that enables us to perform transfusionless complex congenital heart repair targeting patients as small as 5 kg.